Keharmonisan Rumah Tangga Perspektif Muhammad Abduh Tuasikal - Syahwalifa, Yearza Wahdania; Misbahuzzulam, Misbahuzzulam (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
Islamic places significant emphasis on the welfare and prosperity of its followers, necessitating that any legislation enacted must be accompanied by advantageous outcomes. The significance of Islamic teachings is not limited to the domain of worshipping Allah exclusively, but also extends to the realm of human interactions and relationships. As the researcher will discuss, namely the problem of building of harmonious household where all of this has been regulated in Islam. So this writing aims to provide insight regarding tips or tricks so that households can be harmonious up to heaven from the perspective off Muhammad Abduh Tuasikal. The current study utilizes a qualitative research style for data collection by conducting a comprehensive review of scholarly journals, articles, books, and videos authored by Muhammad Abduh Tuasikal. Understanding the responsibilities of one's spouse is one step towards creating a harmonious home, in which the husband must know what his obligations are as well as the wife. The anticipated outcome of this investigation is that it will provide valuable insights to all readers, especially Muslims and as a consideration when there are problems in the household that do not have to end or be resolved by divorce.